Viscoelastic and Viscoplastic Materials 2016
DOI: 10.5772/64170
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelasticity in Foot-Ground Interaction

Abstract: Mechanical properties of the plantar soft tissue, which acts as the interface between the skeleton and the ground, play an important role in distributing the force underneath the foot and in influencing the load transfer to the entire body during weight-bearing activities. Hence, understanding the mechanical behaviour of the plantar soft tissue and the mathematical equations that govern such behaviour can have important applications in investigating the effect of disease and injuries on soft tissue function. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 83 publications
(204 reference statements)
1
4
0
Order By: Relevance
“…This is also indirectly supported by the 121 reported significantly higher heel pad stiffness in people with 122 higher levels of Fasting Blood Sugar [24]. in the clinic [25]. This study by Naemi and co-workers [25] 146 indicated that compared to non-ulcerated group, the ulcer-147 ated group had a significantly lower heel pad stiffness [25].…”
supporting
confidence: 69%
See 1 more Smart Citation
“…This is also indirectly supported by the 121 reported significantly higher heel pad stiffness in people with 122 higher levels of Fasting Blood Sugar [24]. in the clinic [25]. This study by Naemi and co-workers [25] 146 indicated that compared to non-ulcerated group, the ulcer-147 ated group had a significantly lower heel pad stiffness [25].…”
supporting
confidence: 69%
“…in the clinic [25]. This study by Naemi and co-workers [25] 146 indicated that compared to non-ulcerated group, the ulcer-147 ated group had a significantly lower heel pad stiffness [25]. Table 2 shows the categorical parameters including sex, smoking, Oral Hypoglycaemic Agent (OHA) use, insulin only use, OHA & insulin use, history of eye surgery, Edema/swollen feet, tineapedic, onychomycosis, callus, history of ulcer, history of callus and foot shape abnormality for the participants and also for each group.…”
mentioning
confidence: 99%
“…The plantar soft tissue of the foot consists of highly specialized tissues which present with complex nonlinear, visco-elastic mechanical properties in addition to a complex internal structure comprising of both skin and plantar fat pad [1].…”
Section: A Introductionmentioning
confidence: 99%
“…The plantar soft tissue of the foot consists of highly specialized tissues that present with complex nonlinear, viscoelastic mechanical properties in addition to a complex internal structure comprising of both skin and plantar fat pad. 1 Previous studies show that diabetes is associated with changes in the plantar soft tissue mechanical properties as a result of glycation which is associated with an increased blood sugar level over prolonged periods of time. Specifically, the plantar soft tissue in people with diabetes compared with the age-matched groups of people without diabetes is thicker, 2 stiffer, 3,4 harder 5 , and also tends to have less energy return efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of soft tissue deformation is so small that can be neglect compared with that of terrain deformation in the off-road walking occasions. More practically, soft issues at heel pads interacting with rigid ground were often described by non-linear viscoelastic models [32]. The linkages among heel, phalangeal joint, and toe (can be approximated by three spheres [33]) will add viscosity and response delay for the total system.…”
Section: Introductionmentioning
confidence: 99%